Pengaruh Konsentrasi Nutrisi AB Mix Terhadap Pertumbuhan dan Hasil Dua Varietas Melon (Cucumis melo L.) pada Sistem Hidroponik - Wahyudi, Muhammad Ikhsan; Safitri, Betari; Tiara, Dede; Putri, Sekar Utami; Salsabila, Vinni Aurelia (Politeknik Negeri Lampung, 2025)
The use of hydroponic systems is often constrained by high costs due to the relatively expensive price of AB Mix fertilizers. This study aimed to determine the optimal AB Mix nutrient concentration for the growth and yield of two melon varieties, as well as to examine the interaction between AB Mix nutrient concentration and the two melon varieties used. The experiment was arranged in a Randomized Complete Block Design (RCBD) with a split-plot pattern consisting of two factors: AB Mix nutrient concentration (1200, 1500, 1800, and 2100 ppm) as the main plot, and melon varieties Inthanon and Honey Globe as subplots. Data were analyzed using analysis of variance (ANOVA), and significant differences were further tested using the DMRT at a 5% significance level. The results showed that an AB Mix nutrient concentration of 1800 ppm resulted in better growth and development of melon plants compared to other concentrations. Variety V2 (Honey Globe) also exhibited the best performance, particularly in terms of leaf width, fruit diameter, and fruit weight. In addition, there was an interaction between AB Mix nutrient concentration and melon variety affecting plant height at 14 and 21 days after planting (DAP) as well as fruit diameter, indicating that plant responses depended on the combination of both treatments.